PERAN MEDIA DIGITAL E-BRANCH DALAM MENINGKATKAN EFISIENSI WAKTU DALAM BERTRANSAKSI DI BANK CENTRAL ASIA KCP UNDAAN SURABAYA - Sihombing, Cindy Shinta Br; Fadhillah, Is (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study investigates the role of E-Branch digital media in enhancing transaction time efficiency at Bank Central Asia (BCA) KCP Undaan Surabaya, identifies adoption obstacles, and describes features supporting this efficiency. A qualitative descriptive research approach was used, with data collected through interviews with customers and bank employees, observations of E-Branch transaction processes, and related documentation. Data analysis included reduction, presentation, and conclusion drawing. Findings indicate that E-Branch significantly enhances transaction efficiency by allowing customers to input transaction data independently, thus reducing queue times at tellers. Key features contributing to efficiency include minimized manual input, increased transaction speed, queue efficiency, and reduced paper usage. Barriers to E-Branch adoption include customer acceptance variability, educational challenges, potential input errors, infrastructure limitations, employee understanding, and necessary internal process adaptations. Essential features supporting efficiency include reduced manual input, transaction speed, queue efficiency, training and education for employees and customers, and transaction security.